2012
DOI: 10.1161/circep.111.969105
|View full text |Cite
|
Sign up to set email alerts
|

Meta-Analysis of Bleeding Complications Associated With Cardiac Rhythm Device Implantation

Abstract: Background Many patients receiving cardiac rhythm devices have conditions requiring antiplatelet (AP) and/or anticoagulant (AC) therapy. Current guidelines recommend a heparin bridging strategy (HBS) for anticoagulated patients with moderate/high risk for thrombosis. Several studies reported lower bleeding risk with continued oral anticoagulation rather than HBS. The best strategy for perioperative management of patients on AP therapy is less clear. The present study was designed as a meta-analysis of device i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
63
1
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(74 citation statements)
references
References 32 publications
7
63
1
3
Order By: Relevance
“…One‐year follow‐up results of this study showed significantly greater incidence of device‐related infection among patients who developed hematoma versus those without (11.0% vs 1.5%, P <0.001) 14. Further, findings from a meta‐analysis of 19 studies comparing continuous anticoagulation with heparin bridging found similar results to BRUISE CONTROL, with the incidence of bleeding events ranging from 2.2% among those with no anticoagulant therapy to 14.6% with heparin bridging 8. Although our results differ, the findings from our study may represent the best lower bound for the true incidence of pocket hematoma in real‐world practice.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…One‐year follow‐up results of this study showed significantly greater incidence of device‐related infection among patients who developed hematoma versus those without (11.0% vs 1.5%, P <0.001) 14. Further, findings from a meta‐analysis of 19 studies comparing continuous anticoagulation with heparin bridging found similar results to BRUISE CONTROL, with the incidence of bleeding events ranging from 2.2% among those with no anticoagulant therapy to 14.6% with heparin bridging 8. Although our results differ, the findings from our study may represent the best lower bound for the true incidence of pocket hematoma in real‐world practice.…”
Section: Discussionsupporting
confidence: 56%
“…Results from recent retrospective and prospective studies cite a wide range of estimates for the incidence of bleeding complications, ranging from 1.1% to 16% 7, 8, 9, 10, 11, 12, 13. Once bleeding occurs, clinically meaningful pocket hematoma has been linked to a significant increase in perioperative pain and decrease in quality of life 9.…”
Section: Introductionmentioning
confidence: 99%
“…[8] A meta-analysis of patients undergoing device implantation who had not received any anticoagulation reported the incidence of bleeding as 2.2 out of 100 cases. [9] In our two cases, we report examples of rare complications of device implantation due to direct injury to subclavian vein and artery during cephalic vein cut down in the first and during subpectoralis pocket formation in the second case. Iatrogenic brachial plexus injuries from surgery and other medical procedures contribute to about 7 to 10 percent of all brachial plexopathies.…”
Section: Discussionmentioning
confidence: 84%
“…Az elmúlt évtizedekben a procedúrák komplexebbé vá-lása mellett a beavatkozásra kerülő páciensek átlagé-letkorának növekedésével a kardiális és nem kardiális komorbiditásaik számának emelkedése egyaránt hozzájárult a procedúrákkal járó szövődmények számának növekedéséhez. A PM/ICD/CRT-implantációk alapvetően minor sebészeti beavatkozásnak számítanak, és nem magas rizikójúak, de az antitrombotikus kezelés nagymértékben emeli a lehetséges (főként a vérzéses jellegű, illetve ezzel összefüggő) komplikációk arányát (26). A vérzéses szövődmény leggyakoribb formája a generátor zsebben kialakuló vérömleny, amely a páci-ensnek okozott kellemetlenségeken túl jelentős morbiditással és mortalitással járhat, mert növeli a hospitalizáció idejét, költségét, reoperációt tehet szükségessé (közel 50%-ban), jelentősen emeli a késői infekciós szövődmények előfordulási valószínűségét (25,29), és az antitrombotikus kezelés hosszabb idejű felfüggesz-tésének szükségessége miatt még emelkedett tromboembóliás kockázattal is jár.…”
Section: Antikoaguláns Kezelés Katéterablációk Soránunclassified
“…Az acetilszalicilsav monoterápia önmagában másfélszeresére, a kettős trombocitaaggregáció-gátlás közel ötszörösére emeli a vérzéses komplikációk arányát (26). A szekunder prevenciós TAG-monoterápia elhagyása önmagában háromszorosára emeli a tromboembóliás komplikációk arányát (34).…”
Section: Táblázat)unclassified